A taxonomic report of shallow-water holothurians of Calatagan, Batangas - Reyes-Leonardo, Lydia D. (1984)
Twenty-seven species of holothurians belonging to seven genera were collected in Calatagan, Batangas from September 1981 to July 1982. Of the three families represented namely Synaptidae, Stichopodidae and Holothuriidae, th last is the most common (with 20 species). Two species, Holothuria (Theelothuria) klunzingeri Lampert and Holothuria (Theelothuria) notabilis Ludwig are new records for the Philippines. The taxonomic scheme used in this paper follows that of Rowe (1969). All materials are deposited in the Invertebrate Museum of the Marine Science Center, University of the Philippines, Diliman, Quezon City.